Analyzing Perceptual Differences in Spiritual Language Through the Eye Beginning with the Image - Kherodinashvili, Zurab (Utan Kayu Publishing, 2025)
This research study explores the interrelationship between early attachment to primary caregivers, language acquisition, and spiritual development. It examines how key models of language acquisition—Behaviorist, Innate, and Interactionist—contribute to our understanding of linguistic development while highlighting their limitations in addressing the cultural and emotional aspects of language. The study posits that linguistic and spiritual development are interdependent, emerging as universal human capacities. Two core hypotheses are proposed: (1) secure early attachments positively influence spiritual expression later in life, and (2) bilingual individuals experience spirituality differently depending on the language used. To investigate these hypotheses, the study will employ eye-tracking technology to measure physiological responses to spiritual language, offering a more objective alternative to self-reported data. Furthermore, the study will analyze perceptual differences using languages from distinct families—Georgian (Kartvelian family) and English (Indo-European family)—to explore the role of linguistic structure in shaping spiritual perception. This interdisciplinary approach seeks to uncover how preferred language influences spiritual experience, offering deeper insights into the interconnected nature of language, emotion, and spirituality.